Dietary Re-education, Exercise Program, Performance and Body Indexes Associated with Risk Factors in Overweight/Obese Women - Marchini Julio; Fabbro Amaury; Fett Waléria; Fett Carlos (Taylor & Francis Group, 2005)
Abstract This study observed the effect of a dietary re-education plus regular physical activity on body composition, risk factors and physical test performance of sedentary overweight/obese women and to correlate these variables one with each other. Fifty women (36 ± 10 yrs; 31 ± 6 body mass index (BMI, kg/m2)) volunteered for the study. Body compositions were obtained by anthropometry and bioimpedance and some body indexes were established. One-repetition maximum (1-RM) and treadmill VO2max tests were carried out and blood samples were obtained for lipid, glucose and uric acid analyses before (T1) and after two months of intervention (T2). Diet was established by indirect calorimetry. Body fat, glucose, uric acid, total cholesterol, HDL-cholesterol and systolic blood pressure were significantly reduced. The 1-RM and VO2max tests were significantly increased. Neck circumference (NC) was correlated with body composition, back muscle 1-MR, HDL and LDL cholesterol, total cholesterol/HDL ratio, uric acid, and resting energy expenditure. BMI was found to be significantly correlated with waist/hip ratio, circumference sum, and body fat percentage by anthropometry and bioimpedance. Body fat percentage determined by bioimpedance and anthropometry was significantly correlated with arm fat area and arm fat area corrected respectively, and both with BMI at T1 and T2. This study suggests that a dietary reeducation plus physical activity around 200 min/week improved body composition and the health of these women. Many anthropometry measurements have correspondence to risk factors and NC could be a simple approach to reflect these results, without other more complex techniques.